Compliance of Quezon City Public Library, Marikina City Public Library and National Library's Library for the Blind to IFLA guidelines for libraries for persons with disabilities - Diaz, Guadalupe Maxima B. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Public Libraries are heralds of knowledge for all people. These are libraries which cater to the needs of all - students, elderly, professionals, normal citizens and the disabled. These institutions answer the information needs and queries of every citizen, including those who are physically disabled. This study is aimed at evaluating selected public libraries in NCR and assess if these chosen public libraries adhere to the guidelines set by IFLA in terms of the construction and development of public libraries in order to cater physically disabled users.